2021
DOI: 10.48550/arxiv.2108.13964
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Photon control and coherent interactions via lattice dark states in atomic arrays

Oriol Rubies-Bigorda,
Valentin Walther,
Taylor L. Patti
et al.

Abstract: Ordered atomic arrays with subwavelength spacing have emerged as an efficient and versatile light-matter interface, where emitters respond collectively and form subradiant lattice modes with supressed decay rate. Here, we demonstrate that such lattice dark states can be individually addressed and manipulated by applying a spatial modulation of the atomic detuning. More specifically, we show that lattice dark states can be used to store and retrieve single photons with near-unit efficiency, as well as to contro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Hence, the reverse absorption process will result in scattering losses when the lattice is not illuminated symmetrically. When light is incident symmetrically from both sides, it can indeed be absorbed with near-unity efficiency [60] which can be utilized in storing a single photon [28,29]. For multiple layers, as described further in Sec.…”
Section: Absorption In Single Layermentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, the reverse absorption process will result in scattering losses when the lattice is not illuminated symmetrically. When light is incident symmetrically from both sides, it can indeed be absorbed with near-unity efficiency [60] which can be utilized in storing a single photon [28,29]. For multiple layers, as described further in Sec.…”
Section: Absorption In Single Layermentioning
confidence: 99%
“…4(c,d), with a higher efficiency of 0.93. Alternatively, the efficiency could be improved by varying the level shifts in time during the absorption [29]. However, ( the differing level shifts, δ xs = δ xa , mean that each mode evolves at a different frequency, complicating the effect of varying the level shifts over longer timescales.…”
Section: B Photon Absorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent experimental advances in optical lattices [21][22][23] and atomic tweezers [24][25][26], which allow to produce atomic lattices -as well as more complex configurations-with inter-particle spacing of the order of an atomic transition wavelength, have revived the interest in superradiant and subradiant physics. While * orubies@mit.edu these systems have been extensively studied in the case where only one excitation is present in the lattice [27][28][29][30][31][32][33][34], the behavior of inverted lattices is poorly understood. Recent theoretical studies have shown that the appearance of the superradiant burst in inverted samples is determined by the statistics of the first two photons [35,36], or alternatively by the Taylor series expansion of the photon emission rate at time t = 0 [37].…”
mentioning
confidence: 99%